Study of Cold Atmospheric Plasma Jet at the End of Flexible Plastic Tube for Microbial Decontamination - Kostov, Konstantin G. [UNESP]; Nishime, Thalita M. C. [UNESP]; Machida, Munemasa; Borges, Aline C. [UNESP]; Prysiazhnyi, Vadym [UNESP]; Koga-Ito, Cristiane Y. [UNESP] (Wiley, 2015)
Recently, cold atmospheric plasmas have demonstrated very promising antimicrobial activity in vitro and in vivo including selective destruction of tumor cells. However, the size and the rigidity of most plasma systems limit the clinical application for treatments in internal organs or regions with difficult access (e.g., mouth). Here, we report a device that allows ignition of cold He plasma jet at the tip of 1 m long, 3.5 mm diameter, flexible plastic tube. It is connected to a dielectric enclosure where dielectric barrier discharge (DBD) is generated by a low-frequency AC power supply. A thin wire at floating potential put inside the plastic tube assists the formation of plasma jet at the downstream tube end. The flexible tube can be kept and manipulated by hand without electric shock and thus the plasma jet can be easily directed to a target. Variation of duty cycle of the applied voltage signal allows precise adjustment of the discharge power. The anti-microbial efficiency of plasma jet system with flexible tube was tested against fungus Candida albicans seeded on agar.
Keywords: atmospheric plasma jet; C. albicans; decontamination; non-thermal plasma